Co-creation and self-evaluation: An accountability mechanism process in water, sanitation and hygiene services delivery in childcare centres in Nairobi's informal settlements - Ivy Chumo; Caroline Kabaria; Helen Elsey; Kim Ozano; Penelope A. Phillips-Howard; Blessing Mberu (Frontiers Media S.A., 2023)
BackgroundAccountability strategies are expected to enhance access to water, sanitation and hygiene (WASH) service delivery in low-and middle-income countries (LMIC). Conventional formal social accountability mechanisms (SAMs) for WASH service delivery have been inadequate to meet the needs of residents in informal settlements in LMICs. This has prompted growing interest in alternative informal SAMs (iSAMs) in Nairobi's informal settlements. To date, iSAMs have shown a limited effect, often due to implementation failures and poor contextual fit. In childcare centers in Nairobi's informal settlements, co-creation of the iSAMs process, where parents, childcare managers, researchers and other WASH stakeholders, contribute to the design and implementation of iSAMs, is an approach with the potential to meet urgent WASH needs. However, to our knowledge, no study has documented (1) co-creating iSAMs processes for WASH service delivery in childcare centers and (2) self-evaluation of the co-creation process in the informal settlements.MethodsWe used a qualitative approach where we collected data through workshops and focus group discussions to document and inform (a) co-creation processes of SAMs for WASH service delivery in childcare centers and (b) self-evaluation of the co-creation process. We used a framework approach for data analysis informed by Coleman's framework.ResultsStudy participants co-created an iSAM process that entailed: definition; action and sharing information; judging and assessing; and learning and adapting iSAMs. The four steps were considered to increase the capability to meet WASH needs in childcare centers. We also documented a self-evaluation appraisal of the iSAM process. Study participants described that the co-creation process could improve understanding, inclusion, ownership and performance in WASH service delivery. Negative appraisals described included financial, structural, social and time constraints.ConclusionWe conclude that the co-creation process could address contextual barriers which are often overlooked, as it allows understanding of issues through the 'eyes' of people who experience service delivery issues. Further, we conclude that sustainable and equitable WASH service delivery in childcare centers in informal settlements needs research that goes beyond raising awareness to fully engage and co-create to ensure that novel solutions are developed at an appropriate scale to meet specific needs. We recommend that actors should incorporate co-creation in identification of feasible structures for WASH service delivery in childcare centers and other contexts.